Flawed saviours: the myths of Hindenburg and Pétain - von der Goltz, A; Gildea, R (Sage, 2009)
Although Hindenburg and Pétain emerged from very different historical traditions, one monarchical and authoritarian, the other democratic and republican, their trajectories and cults in the twentieth century in fact had much in common. Both emerged as military heroes, saving the fatherland in 1914 in iconic victories, and both were subsequently called back as political saviours as the Weimar and Third Republics ran into difficulties and collapsed. The status and reputation of each was enhanced by a cult that was both manufactured and spontaneous, ranging widely across the political spectrum and reaching deep into the body politic. The cults drew on powerful images of solidity and ancient heroes. Both leaders were, however, flawed, compromising with Nazi power, and they were buried far from the sites of their victories. In spite of these flaws, however, the cults of Hindenburg and Pétain have been remarkably adaptable and enduring.